Mutual Fund Performance: Impact of Stock Market, Interest Rates, and Inflation.: Kinerja Reksa Dana: Dampak Pasar Saham, Tingkat Bunga, dan Inflasi. - Puspita Dwi Aryadi; Wisnu Panggah Setyono (Academia Open, 2022)
This quantitative study investigates the relationship between the Composite Stock Price Index (JCI), interest rates, inflation, and the performance of equity mutual funds listed on the Indonesia Stock Exchange (IDX) during the 2017-2020 period. Secondary data from various literature sources, official websites, and company reports were utilized. Multiple linear regression analysis was employed to analyze the data. The findings reveal that both JCI and interest rates significantly influence the performance of stock mutual funds, whereas inflation exhibits a negative but statistically insignificant effect. Moreover, when considered together, JCI, interest rates, and inflation collectively impact the performance of equity funds. These outcomes highlight the importance of considering macroeconomic factors, specifically the stock market and interest rate dynamics, in assessing and managing the performance of equity mutual funds. Highlights: Stock market and interest rates significantly impact equity mutual fund performance. Inflation has a negative but statistically insignificant effect on mutual fund performance. Considering macroeconomic factors is crucial for assessing and managing equity mutual fund performance. Keywords: Stock Market Performance, Interest Rates, Inflation, Equity Mutual Funds, Indonesia Stock Exchange (IDX).